Developing Workers’ Social Insurance Legislation: Can the Work-Break-Rework Cycle Be Broken? - Yusuf Alper (Sosyal Siyaset Konferansları Dergisi)
The Turkish social insurance system has practically turned into Lego blocks in terms of legislation regulating social insurance rights and obligations with frequent interventions. In the past, Türkiye’s Social Insurance Act No. 506 and Pension Fund Act No. 5434 are single-roof laws that aim to consolidate the disparate social insurance system. Türkiye’s Social Insurance and General Health Insurance Act No. 5510 is also a single-roof law that was prepared and put into effect for the same reasons. However, in the past 16 years since the enactment of Act No. 5510, the need for a comprehensive rearrangement has emerged through the frequent interventions similar to previous periods. In short, the Turkish social insurance system is again on its way to the work-break-rework dilemma.